Validation of risk assessment models for venous thromboembolism in patients with cancer receiving systemic therapies - Nikola Vladić; Cornelia Englisch; Julia M. Berger; Florian Moik; Anna S. Berghoff; Matthias Preusser; Ingrid Pabinger; Cihan Ay (Blood Advances, 2025)
Abstract: Cancer increases the risk of venous thromboembolism (VTE). To identify patients with cancer at high VTE risk who might benefit from primary thromboprophylaxis, several risk assessment models (RAMs) have been developed. The evolution of anticancer treatment, including the implementation of targeted and immunotherapeutic agents, might affect VTE risk and risk prediction. Therefore, we aimed to evaluate the performance of 6 externally validated RAMs (Khorana score, PROTECHT, CONKO, COMPASS-CAT, CATScore, and EHR-CAT) in a prospective observational cohort study of patients with cancer initiating contemporary systemic anticancer therapies. Eight hundred six patients (49.5% female) with a median age of 61 years (interquartile range, 53-69) were included. The most common cancer types were lung (21.8%), breast (10.8%), and pancreatic (10.3%). Anticancer therapies initiated at study inclusion included chemotherapy (48.3%), a combination of chemotherapy and immune checkpoint inhibitor (ICI; 16.6%), ICI monotherapy (15.4%), and targeted agents (19.7%). During an observation period of 6 months, 91 patients experienced a VTE (cumulative incidence, 11.2%; 95% confidence interval [CI], 9.0-13.3). The discriminatory performance of the RAMs varied, with the best c-statistic seen with the CAT Score, whereas the COMPASS-CAT score showed the lowest area under the curve value (c-statistics: Khorana score, 0.53 [95% CI, 0.50-0.56]; PROTECHT, 0.58 [95% CI, 0.56-0.61]; CONKO, 0.54 [95% CI, 0.51-0.57]; COMPASS-CAT, 0.50 [95% CI, 0.47-0.53]; CAT Score, 0.65 [95% CI, 0.62-0.67]; EHR-CAT, 0.55 [95% CI, 0.52-0.57]). Overall, we observed a poor to modest discriminatory performance of the RAMs in our contemporary cohort of patients with cancer, with the CAT Score performing best among all evaluated scores.